The effects of different coculture patterns with salt-tolerant yeast strains on the microbial community and metabolites of soy sauce moromi. (December 2021) - Zhang, Lin; Huang, Jun; Zhou, Rongqing; Qi, Qi; Yang, Menglu; Peng, Can; Wu, Chongde; Jin, Yao
Graphical abstract: Highlights: The inoculated strain and sequence affected metabolites and microbial communities. Yeasts' strain-level specificity existed whether single culture or co-culture model. Volatiles were more easily formed when Z. rouxii inoculated before C. versatilis . Ketones' content increased the most by inoculating Z. rouxii QH-25 preferentially. Co-culturing of Z. rouxii and C. versatilis altered the interaction of microbes. Abstract: In this study, the contributions of three strains and different coculture patterns to microbial community diversity and metabolites in the high-salt liquid-state fermentation (HLF) soy sauce moromi were investigated. A comparison of two strains of Zygosaccharomyces rouxii showed that strain QH-25 had a stronger ability to contribute metabolites, including both nonvolatile and volatile types, to the moromi than strain QH-1, except for volatile acids and ketones. Of the various fortification patterns tested, the content of metabolites was significantly increased by inoculating Z. rouxii QH-25 prior to C. versatilis, especially the content of volatiles, including ketones, esters, phenols, and alcohols, which increased 1.61-fold compared with those in the control sample; the contents of these components were increased 3.07-, 1.91-, 1.36-, and 1.22-fold, respectively. In particular, characteristic components such as ethyl octanoate, 4-hydroxy-2(or 5)-ethyl-5(or 2)-methyl-3(2H)-furanone (HEMF), 4-ethyl-2-methoxy-phenol (4-EG), and 3-methyl-1-butanol were increased 3.99-, 3.29-, 1.63-, and 0.70-fold, respectively. Redundancy analysis (RDA) showed that Staphylococcus, Zygosaccharomyces, and Candida were positively correlated with the unique components described above. In addition, the nodes of the interaction network between Zygosaccharomyces and Candida were increased, and the positive correlation of Zygosaccharomyces with Staphylococcus was enhanced by inoculating Z. rouxii prior to C. versatilis . These results suggested that the unique flavor of soy sauce was closely related to the metabolic characteristics of strains affiliated with Z. rouxii, whether cultured singly or cocultured with C. versatilis . This study also provided a reference method for determining the differences in community structure and metabolites between traditional techniques and modern processes for soy sauce fermentation.